Applying E-learning in Teaching Philosophy according to the Perspectives of its Instructors - Dali, Hammam Taha; Saifuddin, Emad (Journal of Tikrit University for Humanities, 2023)
The study aimed to identify the role of applying e-learning in teaching philosophy from the point of view of its teachers in secondary schools of Salah al-Din Governorate. The researcher used the analytical descriptive approach where the original community consisted of teachers of philosophy for the secondary stage، the study sample included (165) teachers and schools، where a questionnaire was designed by the researcher on the requirements of teaching philosophy through e-learning، and the validity and stability of the questionnaire was verified by statistical means required، after performing the statistical analysis of the data. The results showed that there are various applications for the use of e-learning in teaching philosophy، and that e-learning is of great importance in increasing academic achievement and improving the thinking levels of learners in it. And the educational qualification، and the existence of differences attributed to the variable of the teacher's teaching experience and the variable of undergoing training courses in favor of those who underwent training courses.